ENTREPRENEURSHIP, SUPPORT OF THE ECONOMIC CHANGES IN CHINA - Vlăduț-Severian IACOB; Alexandru NEDELEA (USV Annals of Economics and Public Administration, 2014)
Viewed as an extremely tempting and complex topic, entrepreneurship is still a young, emerging field of study with a low paradigmatic evolution which arises strong interest among researchers, practitioners and political deciders. The detailed examination of the multiple nature of entrepreneurship has revealed the manifestation of more analysis stages, each of these contributing to a deeper understanding of the field. The focus of the studies was directed mainly to the individual, corporations and nations. The research of entrepreneurship at an individual level focuses on the people’s entrepreneurial skills, on their ability to take risks and other personal particularities. The analysis of the corporate level of entrepreneurship emphasizes the companies’ potential to develop strategies to ensure their existence in the business field. At national level, entrepreneurship seen as a result of culture, research-development, access to financing and technology can be considered the ”engine” of economic growth and poverty reduction. The present study wishes to combine all these aspects to argument the force of entrepreneurship in China, a country with an economy in transition, where, in the last three decades, an assumed economic development was registered. Thus, it is shown that at individual level, the Chinese entrepreneurship focuses on entrepreneurial education that is closely related to individuals’ intentions. The corporate level is captured through the evolution of generations of entrepreneurs and their concepts regarding the development strategies of their companies. At national level, the development of entrepreneurship has completed on behalf of the Chinese government’ s efforts to ensure an economic friendly environment , a better life standard, a coherent education reform, a change of business attitude and the regional economic opening.